(untitled) (International journal of artificial intelligence, 2024)
Educational practice is important in enriching students' theoretical knowledge with practical skills and preparing them for professional activities. Organization of educational practice on the basis of cooperation helps to increase the quality of the pedagogical process, to develop students' creative thinking and to form teamwork skills. Pedagogical technologies of organizing educational practice on the basis of cooperation are analyzed in this study.